Investigation of the dosimetric impact of a Ni-Ti fiducial marker in carbon ion and proton beams - Herrmann, Rochus; Carl, Jesper; Jäkel, Oliver; Bassler, Niels; Petersen, Jørgen B. B. (Acta oncologica, 2010)
Introduction. Fiducial markers based on a removable stent are currently used in image guided radiotherapy. Here it is investigated what the possible dosimetric impact of such a marker could be, if used in proton or carbon ion treatment. Material and methods. The simulations have been done using the Monte Carlo particle transport code FLUKA with its default hadron therapy settings. A 3 cm long stent is approximated in FLUKA by stacking hollow tori. To simulate realistic clinical conditions a field 5 × 5 cm has been used, delivering a 5 cm wide spread out Bragg peak located 5 cm deep for protons and carbon ions. For protons fields mimicking active and passive beam delivery have been investigated. The stent has been arranged perpendicular, turned 45 degrees, and parallel to the beam axis. Results. The position of the 95% dose level shifts for carbon ions 7 mm in proximal direction for the marker perpendicular to the beam and 8 mm if the stent is turned 45 degree for a 1 × 1 cm dose binning on the centre beam axis. For the case where the stent was parallel to beam direction the 95% dose level shifts 26 mm. For active delivered protons, the shift of the 95% dose level is less. The shift for a perpendicular arranged marker is 6 mm, for 45 degrees turned it is 7 mm. For the case where the stent was oriented parallel to the beam, the observed shift is 21 mm. Dose inhomogeneities caused by straggling effects occur only near the distal edge of the field. Conclusions. The results of our investigations show that the Ni-Ti marker has a non negligible impact on the dose distributions for the used radiation types. However if the treatment plan rules out narrow angles between symmetry axis of the stent and the beam direction, this may be compensated.
Gesehen am 03.05.2023